The Result of Improving Health Literacy for Reducing Risk of Cardiovascular Disease. A case Study of People living in Amphoe Soem Ngam, Lampang Province - Yotkasem, Sommart; Poodla, Nongphakha (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2024)
The quasi-experimental research aims to study a result of improving health literacy for reduce cardiovascular risk. Research design was two groups pretest-posttest design. Purposive sampling was used to recruit 80 participants who had low, moderate, and high levels of CVD risk and poor and low health literacy levels. Forty of the experimental group receivedan improving health literacy promotion programme in order to reduce risk of cardiovascular disease. The control group received a regular health literacy promotion programme. Research tools were health literacy and self-care behaviour questionnaires, Thai CV risk score and personal health data. The content validity of all instruments were showed by IOC= 0.67-1.00 Quantitative data was analysed using descriptive statistics and Independent T-test and Dependent T test. The results showed that at post-experiment the experimental group had significant higher mean scores of heath literacy and health behaviour (p<0.05), and CVD risk score had significant lower mean scores than at pre-experimental (P<0.05). CVD risk score of experimental group were significant decreased more than control group at post-test (P<0.05).Research suggests that should be used Improving Health Literacy program for Reducing Cardiovascular Risk of all severity of risk and evaluate long term health outcomes.